High w-3 Fatty Acid Eggs Produced by Laying Hens Fed with Sardine Oil - Umar Santoso; M. Nur Cahyanto; Dwi Sulistiawati; Zuprizal Zuprizal; Hari Eko Irianto (Indonesian Food and Nutrition Progress, 1999)
The objective of the present research was to examine the effects of feeding laying hens with sardine oil on the co-3 fatty acids levels of the egg yolk. Results of the study show that changes in the composition of the diet influenced the fatty acid composition of the yolk lipid. Diets with sardine oil from 2 to 8% significantly increased co-3 PUFAs content of the yolk. The increase of w-3 PUFAs was predominated by docosahexaenoic acid (DHA); followed by eicosapentaenoic acid (EPA), and a-linolenic acid (ALA). In term of egg weight basis, the increase of 0-3 PUFAs in egg due to sardine oil consumption. .was from 8.17mg/egg in diet without sardine oil to 102.27 mg/egg in diet with 2% sardine oil, and 232.63mg/egg in diet with 8% sardine oil. (0-6 PUFAs especially arachidonic acid tended to decrease with the increasing intake of sardine oil. Diets with sardine oil significantly (P<0.05) decreased the cholesterol content of the yolk compared to that without sardine oil. Cholesterol content of the eggs produced by laying hens fed with 2% sardine oil was 191.73 mg/egg significantly lower than that of egg produced by laying hens fed without sardine oil. The cholesterol content of 179.74 mg/egg was produced by hens fed with diet containing 8% sardine oil, this was lower that that of egg produced by the commercial feed of 208.09 mg/egg.